A FPGA-based deep packet inspection engine for network intrusion detection system - Thinh, Tran Ngoc; Hieu, Tran Trung; Dung, Van Quoc; Kittitornkun, Surin (My University, 2012)
Pattern matching has became a bottleneck of software based Network Intrusion Detection System (NIDS) as the number of signature have recently increased dramatically. Many FPGA-based architectures for detecting malicious patterns have been proposed recently. However, these approaches have just considered matching pattern separately while more and more complex combination of several patterns are utilized to describe intrusion activities. In this paper we present our work which concentrates on multi-pattern signature and propose a FPGA-based deep packet inspection engine for NIDS. The system can support both static and dynamic patterns. We employ Snort signature set and realize our system on NetFPGA platform. The evaluation on real network environment shows that our system can maintain gigabit line rate throughput without dropping packets. © 2012 IEEE.
Keywords: cuckoo hashing; DPI; FPGA; multi-pattern matching; NFA; NIDS/NIPS; Regular Expression